A Rare Case Report of Caesarean Scar Ectopic Pregnancy - Deepika; Taru Gupta; Sonika Wahi (Journal of Clinical and Diagnostic Research, 2017)
Caesarean scar ectopic is one of the rarest of all ectopic pregnancies. It is defined as when a blastocyst implants on a previous Caesarean scar. The incidence of Caesarean scar ectopic has increased due to increase in number of Caesarean deliveries. Early diagnosis of this can be done by using sonography. It is very important because a delay can lead to increased maternal morbidity and mortality. Early diagnosis leads to prompt management and improves the outcome by allowing preservation of future fertility. Magnetic Resonance Imaging (MRI) has important role when sonography is equivocal or inconclusive before therapy or intervention. We are reporting a rare case of G3P2l2 with previous two Caesarean deliveries, diagnosed as Caesarean scar ectopic pregnancy with the help of sonography and MRI. Patient underwent laparotomy and on histopathological examination Caesarean scar pregnancy was confirmed.